Modelling mesophilic-thermophilic temperature transitions experienced by an aerobic membrane bioreactor treating furfural plant effluent - Kay, LG; Brouckaert, CJ; Sindall, RC (Water SA, 2019)
A mathematical model was developed of an aerobic membrane bioreactor (MBR) treating effluent from a by-products facility at a sugar mill producing furfural, based on measurements of microbial kinetics and stoichiometry at different temperatures. The model was calibrated and validated against plant data using volumetric flow into the MBR and volumetric sludge wasting from the MBR as inputs.  The model is able to predict steady-state and unsteady-state operation of the MBR under both mesophilic and thermophilic conditions, and the transitions between the two regimes.  Comparison of model simulations and plant data suggests that thermophilic operation is advantageous, but it is less stable than mesophilic operation and frequent feed disruptions can have detrimental effects on MBR operation.